2003
DOI: 10.1097/01.psy.0000074003.35911.41
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Stress Reduction in Relation to Quality of Life, Mood, Symptoms of Stress, and Immune Parameters in Breast and Prostate Cancer Outpatients

Abstract: MBSR participation was associated with enhanced quality of life and decreased stress symptoms in breast and prostate cancer patients. This study is also the first to show changes in cancer-related cytokine production associated with program participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
482
3
12

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 643 publications
(535 citation statements)
references
References 61 publications
38
482
3
12
Order By: Relevance
“…developed and manualized MBCR 32 specifically to meet the needs of oncology populations, and its efficiency has been validated in previous studies. [33][34][35][36][37][38][39] Facilitators were clinical psychologists and a nurse who were fully trained in mindfulness-based stress reduction and had led groups in previous MBCR trials. Participants attended 8 weekly group sessions of 90 minutes in duration, and a six-hour retreat between weeks 6 and 7.…”
Section: Interventionsmentioning
confidence: 99%
“…developed and manualized MBCR 32 specifically to meet the needs of oncology populations, and its efficiency has been validated in previous studies. [33][34][35][36][37][38][39] Facilitators were clinical psychologists and a nurse who were fully trained in mindfulness-based stress reduction and had led groups in previous MBCR trials. Participants attended 8 weekly group sessions of 90 minutes in duration, and a six-hour retreat between weeks 6 and 7.…”
Section: Interventionsmentioning
confidence: 99%
“…There is preliminary evidence that TNF blockade with etanercept is safe and effective in reducing fatigue among patients with advanced cancer (Monk et al, 2006), but effects among patients with early stage cancer and cancer survivors have not been determined. Behavioral and mind-body interventions also show considerable promise for treating fatigue and other cancer-related symptoms, and there is preliminary evidence for their effects on immune function (Carlson et al, 2003;Fairey et al, 2005). These treatments may be more palatable to cancer patients than pharmacologic therapies and are another important avenue for research efforts.…”
Section: Conclusion and Recommendations For Future Researchmentioning
confidence: 99%
“…As many studies have reported effectiveness of Asana-Pranayama as well as silent meditation and chanting these were used to enhance natural, inherent healing processes [5,7,8,10,13,16].…”
Section: Modes Of Reintegrationmentioning
confidence: 99%
“…Keeping this in mind and other reports on possible effectiveness of Yoga, meditation and mindfulness as rehabilitative/palliative therapy in cancer, [6][7][8][9][10][11][12][13][14] Kaivalyadhama Yoga Institute in Lonavla, India initiated a three week residential intensive retreat for cancer survivors to enable them to regain their health and wellbeing [15]. The comprehensive curriculum of this " Rejuvenation Retreat for Cancer Patients" includes an integrative approach utilising Asana, Pranayama, meditation, mindfulness, chanting, Yoga Nidra as well as Kirtan Kriya.…”
Section: Introductionmentioning
confidence: 99%